Perkawinan Dalam Perspektif Hukum Islam dan Hukum Positif - Tasyukur; Yustisi, Nabhani (Enlightenment Publishing, 2024)
Marriage in Islamic law and positive law creates various issues within society, leading to many individuals not fulfilling administrative requirements as stipulated by law. For instance, marriages must be registered at the Office of Religious Affairs, and divorces must be processed through the Religious Court. Based on these problems, the author is interested in examining